Guru Profesional Dalam Revolusi Indutri 4.0 Di SMKS Manbaul Ulum Cirebon: Tantangan Dan Peluang - Titi Maryati; Suklani Suklani (Departement of Mathematics Education, 2024)
There are 4 competencies for a teacher to be said to be professional, namely professional competence, pedagogical competence, social competence. Apart from having to have competence in the professional field, professional teachers must also have competence in the teaching/abilities that he must have include, first, competence for technology commercialization, competence in globalization, competence in future strategy, counselor competence. Industrial Revolution 4.0 in the field of education is defined as the use of technology in the context of the teaching and learning process. This aims to equip graduates with the skills and competencies needed by digital-based industries. The aim of this research is to find out the picture of Professional Teachers in the Industrial Revolution 4.0: Challenges and Opportunities. Namely professional teachers in the Industrial Revolution 4.0 era and this research was conducted at one of the Manbaul Ulum Vocational Schools in Cirebon. The data collection technique in this research uses instruments; Direct observation, interviews, and use of observation sheets with a qualitative descriptive design. As well as involving professional teachers as resource persons. The findings of this research indicate that teacher professionalism in the Industrial Revolution 4.0 at SMKS Manbaul Ulum Cirebon is good. Professional teachers have challenges and opportunities. In this research, a professional teacher is required to develop content in the Industrial Revolution 4.0, Hack the Classroom, Able to use Learning Applications 4.0, Literacy Era 4.0, Understand Teaching Trends in 4.0, Use STEAM learning, Use online for learning assessment and educate in accordance with developments over time. And the opportunities in teaching in the Industrial Revolution 4.0 are to provide flexible learning time and place, increase the self-confidence and motivation of a professional teacher, encourage independence, increase creativity, build meaningful English learning, prepare graduates for the world of work and life in the world Work. future, creating opportunities for professional teachers to involve technology in the learning process.